Comprehension of in-service primary-science teachers toward 21st century skills: A case study on Purwakarta. Issue 4 (February 2019) - Handayani, H; Sopandi, W; Syaodih, E; Suhandi, A; Maftuh, B; Hermita, N; Somantri, M; Samsudin, A
Abstract: Twenty-first-century skills usually are going neglected by several primary teachers (in-service teachers) in term of the learning process rather than students' achievement. Though the implementation of information-acquisition theory this research aims to explore primary teachers' perceptions toward 21st-century skills. The research method which was utilized as a case study with respondents was about tenth in-service primary teachers from five schools in Purwakarta city. The data were been collected through semi-structural interview and analyzed using grounded theory. The research results show that primary teachers need to comprehend 21st-century skills regarding develop primary students' learning. Furthermore, they also explain the complexity of teachers which were facing and developing their 21st-century skills. As a consequence, this research promotes the educational training for primary teachers to develop twenty-first-century skills in primary context.